2016
DOI: 10.1111/1751-7915.12433
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Mycobacterium smegmatis for testosterone production

Abstract: SummaryA new biotechnological process for the production of testosterone (TS) has been developed to turn the model strain Mycobacterium smegmatis suitable for TS production to compete with the current chemical synthesis procedures. We have cloned and overexpressed two genes encoding microbial 17β‐hydroxysteroid: NADP 17‐oxidoreductase, from the bacterium Comamonas testosteroni and from the fungus Cochliobolus lunatus. The host strains were M. smegmatis wild type and a genetic engineered androst‐4‐ene‐3,17‐dion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 67 publications
2
40
0
Order By: Relevance
“…It has been demonstrated that M. smegmatis mc 2 155 is able to transport efficiently different C‐19 steroids (e.g. AD) (Fernández‐Cabezón et al ., 2017) and hence, the inability to use C‐19 steroids as carbon sources cannot be due to transport problems. Therefore, we ascribed this behaviour to the fact that the cholesterol pathway might be more tightly regulated in M. smegmatis mc 2 155 than in other C‐19 steroid degrading bacteria, and thus, these compounds might be metabolized only after the complete activation of the kstR regulon that only responds to some CoA‐derivatives of the side chain as inducers (García‐Fernández et al ., ; Ho et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that M. smegmatis mc 2 155 is able to transport efficiently different C‐19 steroids (e.g. AD) (Fernández‐Cabezón et al ., 2017) and hence, the inability to use C‐19 steroids as carbon sources cannot be due to transport problems. Therefore, we ascribed this behaviour to the fact that the cholesterol pathway might be more tightly regulated in M. smegmatis mc 2 155 than in other C‐19 steroid degrading bacteria, and thus, these compounds might be metabolized only after the complete activation of the kstR regulon that only responds to some CoA‐derivatives of the side chain as inducers (García‐Fernández et al ., ; Ho et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Hasan [54] and Fernández Cabezón et al [55] reported that various fungi species like Aspergillus flavus, A. ochraceus, Gibberella zeae, Cladosporium cladosporioides, Penicillium funiculosum, and P. rubrum were capable of producing high amount of hormones. Many research studies indicated that gut microflora had a great role in estrogen and phytoestrogen production [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…Engineered strains able to produce testosterone by biotransformation of phytosterols were recently established in Mycobacteria [ 25 ]. A Mycobacterium smegmatis with stably overexpressed HSD3B from Comamonas testosteroni and from Cochliobolus lunatus was used ( Figure 2 ), however significant amounts of testosterone were not yet obtained.…”
Section: Recent Developments In Microbial Biotransformationmentioning
confidence: 99%